2022
DOI: 10.1149/1945-7111/ac7258
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale Multi-Technique Characterization Approach for Analysis of PEM Electrolyzer Catalyst Layer Degradation

Abstract: Polymer electrolyte membrane water electrolyzers (PEMWEs) are devices of paramount importance, enabling the large-scale storage of hydrogen. A transition towards lower catalyst loadings and intermittent operation is needed for widespread utilization, but the extent of degradation of catalyst layer constituents and further structural changes have not been widely explored. The multitude and complexity of degradation mechanisms requires characterization that can explore surfaces and interfaces at a range of lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 107 publications
1
17
0
Order By: Relevance
“…On the other hand, we recently reported an initial increase followed by a stabilization of Ir amount in the closed anode loop when the PEMWE tests were performed in a metal-free setup . The migration of dissolved Ir species through the membrane and the cathode catalyst layer (CCL) has so far been studied through physicochemical characterization of the aged MEAs, with the main focus being placed on the ACL/membrane interface. ,, It was shown that Ir dissolved from the ACL diffuses through the membrane to the CCL, forming an IrO 2 band adjacent to the ACL, precipitating with the dissolved Pt ions within the membrane and even depositing in the cathode. , …”
Section: Correlation Between Electrochemical Cell Performance and Cat...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, we recently reported an initial increase followed by a stabilization of Ir amount in the closed anode loop when the PEMWE tests were performed in a metal-free setup . The migration of dissolved Ir species through the membrane and the cathode catalyst layer (CCL) has so far been studied through physicochemical characterization of the aged MEAs, with the main focus being placed on the ACL/membrane interface. ,, It was shown that Ir dissolved from the ACL diffuses through the membrane to the CCL, forming an IrO 2 band adjacent to the ACL, precipitating with the dissolved Pt ions within the membrane and even depositing in the cathode. , …”
Section: Correlation Between Electrochemical Cell Performance and Cat...mentioning
confidence: 99%
“…28 The migration of dissolved Ir species through the membrane and the cathode catalyst layer (CCL) has so far been studied through physicochemical characterization of the aged MEAs, with the main focus being placed on the ACL/membrane interface. 16,29,30 It was shown that Ir dissolved from the ACL diffuses through the membrane to the CCL, forming an IrO 2 band adjacent to the ACL, precipitating with the dissolved Pt ions within the membrane and even depositing in the cathode. 16,31 To further understand and accurately quantify anode catalyst losses under realistic PEMWE conditions, our aim in this work was to (i) investigate and explain IrO x dissolution pathways in a model electrolyzer cell, (ii) define the total mass balance of Ir lost from the ACL at the end-of-test (EoT) and the uncertainties of the quantification methods used, and (iii) scrutinize the discrepancy between Ir dissolution studies in AMS and MEA systems.…”
mentioning
confidence: 99%
“…When looking at IrO x electrocatalysts for PEMWE, utilizing mosaic TXM imaging gives a visual representation of a largescale area of the catalyst layer, assisting in identification of morphological heterogeneities, in this case clearly showing areas with larger features that are present in addition to the rest of the material that consist of smaller particles that are smaller than resolution of TXM (Figure 9). In 2022, Zaccarine et al 83 used XANES in combination with TXM to identify larger particles as mainly metallic Ir, while the rest of the material is iridium oxide. The large change in adsorption shown by the L 3 edge of the various Ir chemistries in the catalyst in comparison with the zero change in adsorption seen with other catalyst layer species (C, O, F, and S) allows the catalyst to be visualized without other interferences, such as ionomer interference.…”
Section: Iibi X-ray Ct With Xanesmentioning
confidence: 99%
“…(d) Example distribution of each standard species in the same region as the chemical map. [Reprinted from ref . Open access under Creative Commons CC BY license.…”
Section: Why We Need X-ray Ct In Electrocatalysismentioning
confidence: 99%
“…In addition, by varying the incident X-ray energy around the absorption edge of the target element, TXM can be extended to X-ray absorption fine structure (XAFS) imaging, enabling the spatially resolved analysis of the chemical state and local coordination structure of elements. TXM–XAFS measurements have successfully visualized the reaction distribution and degradation progression during charging and discharging inside a cathode layer and active material particles. However, the cathode, electrolyte, and anode in an LiB system join to cause an electrochemical reaction. Therefore, it is important not only to individually analyze each element but also to analyze the reaction and degradation behavior of each element while simultaneously observing the entire battery.…”
Section: Introductionmentioning
confidence: 99%